In situ temperature calibration for critical applications near ambient. (13th January 2020) - Webster, E; Clarke, David; Mason, Ross; Saunders, Peter; White, D Rod
Abstract: Many agricultural, medical and food storage applications require both accurate and reliable knowledge of the temperature to guarantee quality and enable sound decision making. For example, grape growers incur large costs when they are not able to accurately predict frosts; vaccine and blood products need to be stored within a known temperature range, and the longevity of many food goods depends on stable storage temperatures. Although many systems offer accurate temperature measurements for these applications, these systems are often exposed to conditions that may compromise either the sensor or the measurement equipment, often without the knowledge of the user. To provide on-going confidence in automated temperature logging systems, a low-cost, robust and easy-to-use after-market solution is needed. One such solution is based on organic phase-change materials, which are inexpensive, have low toxicity and are demonstrated to provide highly repeatable transition temperatures. By attaching a small vial of the chosen material to an existing temperature sensor, a brief plateau can be induced as the temperature changes, signalling a known temperature to the control system or user. This repeatable temperature 'marker' provides ongoing assurance that the temperature monitoring system is operating correctly. In this study, several promising materials are trialled in the range of 1 °C to 7 °C. Initial results show the method to be a practicable and affordable addition to critical monitoring and control systems.